Preliminary studies of the effect of aerosols on nitrogen dioxide photolysis rates in the city of São Paulo, Brazil - de Miranda, Regina Maura; Andrade, Maria de Fátima; Fattori, Artemio Plana (Atmospheric research, 2005)
The main purpose of this study was to perform a first evaluation of the particles and optical parameters influence on photolysis rates in the city of São Paulo, Brazil. In order to achieve this objective an AERONET (AErosol RObotic NETwork—an inclusive federation of ground-based remote sensing aerosol networks) database and TUV (Tropospheric Ultraviolet Visible) model were used to calculate photolysis rates on cloudless days during specific periods (July and August) of the 2002 winter season. The main sources of ozone precursors in MASP (Metropolitam Area of São Paulo) are the burning of fuels—gasoline, ethanol and diesel. This blend of fuels generates a unique photochemical problem. Also in MASP the concentrations of inhalable particles (PM 10) usually exceed the national standard of 150 μg m −3 for 24 h. It is described that the concentration of particulate matter affects the ozone formation, by its interaction with incident radiation and consequently affecting the photolysis rates. It is very important to have a good description of the behavior of these compounds, not only in the surface, but also in the whole column. This study presents the first results related to this subject. To characterize the influence of different particles in the photolysis rates, results were correlated to aerosol composition. Particles that are mostly composed of black carbon had a high impact, decreasing photolysis rates when their concentrations were high. Aerosol optical properties analyzed as single-scattering albedos were found to participate significantly in the reduction of photolysis rates. It was observed that urban aerosols in São Paulo reduce both photolysis rates (round 15%) and ozone concentrations. Comparing July and August, photolysis rates were lower in July due to solar position.